Catastrophic and Critical Intraoperative Events during Pediatric Craniofacial Surgery. Issue 1 (23rd January 2023) - Kennedy, Diana; Novak, Christine B.; Phillips, John H.; Der, Tara; Forrest, Christopher R.
Abstract : Background: Pediatric craniofacial surgery performed in tertiary care centers by dedicated teams is associated with high levels of safety and low rates of mortality. However, catastrophic and life-threatening events may occur as a result of surgical management of these complex patients. This study reviewed the incidence and acute outcomes of catastrophic and critical events during craniofacial surgery at a single high-volume center. Methods: The data reviewed included the operative procedures of two senior craniofacial surgeons over an 18-year period at a tertiary care pediatric craniofacial center. Catastrophic or critical intraoperative events were defined as events requiring the activation of an emergency code during surgery. The operative details and acute outcomes were reviewed and analyzed. Results: This study reviewed 7214 procedures performed between January 2002 and January 2019. There were 2072 (29%) cases classified as major craniofacial procedures (transcranial, mixed trans-and-extracranial, or major extracranial facial osteotomies), and code events occurred in 14 cases (0.67%; one in 148 patients): venous air embolism (n = 4), cardiac complications (n = 3), major hemorrhage (n = 3), trigeminocardiac reflex (n = 2), acute intracranial hypertension (n = 1), and acute airway obstruction (n = 1). Two cases (14%) experienced a critical event that was anesthesia-related. Cardiac arrest requiring compressions and/or defibrillation was necessary for eight patients. There were no mortalities. Surgery was curtailed in seven cases and successfully completed in seven patients. Conclusions: Catastrophic life-threatening events during pediatric craniofacial surgery are, fortunately, rare. In our institution, experienced teams in the management of catastrophic and critical intraoperative events during major pediatric craniofacial procedures resulted in no mortalities.